A study on the effectiveness of the child act 2001 in educating child offenders / Nadia Ridzuan…[et al.] - Ridzuan, Nadia; Baharim, Baharudin; Mohsin, Putri Samihah; Abdul Rahim, Nurnabila (2009)
Our research on the effectiveness of the Child Act 2001 in educating child offenders focuses on whether the punishment or rehabilitation measures are more efficient in deterring the child offenders and also to suggest ways to enhance the efficacy of the laws in educating them. We looked into the involvement of participants in the programs held in the Henry Gurney School and Tunas Bakti School. Our sources for this research is the Child Act 2001 and other relevant statutes as well as decided cases, books regarding implementation of the law in educating them, articles regarding all the issues involving these child offenders. The adopted method used was more in qualitative approach as our type of study is of a social legal nature. We gathered the bulk of our findings were based from interviews from Magistrates of Court for Children, Social Welfare Officers, Prison Department and also one child offender. The findings revealed that the preferred philosophy in educating child offender is of rehabilitative measure and we have provided alternatives in our conclusions and recommendations. Finally, we believed we have achieved our research objectives as to effectiveness of the Child Act 2001 in educating child offenders in hope that this research will assists policy makers in improving the social justice system of child offenders.